Interaction of Microglia and Astrocytes in the Neurovascular Unit - Liu, Li-rong; Liu, Jia-chen; Bao, Jin-shuang; Bai, Qin-qin; Wang, Gai-qing (Frontiers in Immunology, 2020)
The interaction between microglia and astrocytes significantly influences neuroinflammation. Microglia/astrocytes, part of the neurovascular unit (NVU), are activated by various brain insults. The local extracellular and intracellular signals determine their characteristics and switch of phenotypes. Microglia and astrocytes are activated into two polarization states: the pro-inflammatory phenotype (M1 and A1) and the anti-inflammatory phenotype (M2 and A2). During neuroinflammation, induced by stroke or lipopolysaccharides, microglia are more sensitive to pathogens or damage, thus initially activated into M1 phenotype, and produce the common inflammatory signals such as IL- 1 and TNF-α to trigger reactive astrocytes into A1 phenotype. These inflammatory signals can be amplified not only by the self-feedback loop of microglial activation, but also by the unique anatomy structure of astrocytes. As the pathology further progresses, resulting in local environmental changes, M1-like microglia switch to M2 phenotype and M2 crosstalk with A2. While astrocytes communicate simultaneously with neurons and blood vessels to maintain the function of neurons and the blood-brain barrier (BBB), their subtle changes may be identified and responded by astrocytes, and possibly transferred to microglia. Although both microglia and astrocytes have different functional characteristics, they can achieve immune “optimization” through their mutual communication and cooperation in NVU and build a cascaded immune network of amplification.